AN ANALYSIS ON TEACHING AND LEARNING PROCESS IN ENGLISH CLASS AT SEKOLAH ALAM TANGERANG MEKAR BAKTI JUNIOR HIGH SCHOOL - Kintan Saraswati; Aidil Syah Putra; Dyah Supraba Lastari; Nargis - - (Universitas Muhammadiyah Tangerang, 2022)
Teaching and learning process is a process that contains a series of actions of teachers and students based on reciprocal relationships that take place in educational situations to achieve certain goals. Nature School is one of the alternative educations that use nature as the main media for student learning. This research aimed to find out the teaching and learning process in English class at Sekolah Alam Mekar Bakti Tangerang. The research questions were: how was the teaching process in English class?; how was the learning process in English class?; what are the advantages and disadvantages of teaching and learning process in Nature School setting. Data collection techniques used by researchers are observation, documentation, and interviews. The researchers used a triangulation method. The results showed that: the teachers applied three stages (pre-instructional stage, instructional stage, and follow-up phase); students experienced three stages in their learning process (receiving information, Information storage, and recalling information); there are some advantages and disadvantages found during the teaching and learning process in Nature School setting.